Validação do sistema internacional de detecção e avaliação de cárie (ICDAS II) e do método de fluorescência a laser (DIAGNODENT®) no diagnóstico de lesões de cárie em superfície oclusal: um estudo in vivo - Fernanda Vaz de Melo Diniz Cotta (2011)
This study investigated in vivo the validity of the ICDAS II (International Caries Detection and Assessment System) severity and activity criteria and the laser fluorescence (DIAGNOdent®) in the diagnosis of occlusal caries in permanent teeth. Patients with erupted third molars were selected in the Clinical of Surgery, School of Dentistry, Federal University of Minas Gerais. One calibrated examiner (Kw(severity) ≥ 0.67; K(activity) ≥ 0.70) performed the visual examination using the ICDAS II and using the DIAGNOdent®. Histological criteria of Ekstrand et al.(1998) and methyl red dye were used as gold standard for validation of caries lesions severity and activity respectively.The validity of the methods was determined at different cut-off points D1, D2, D3. The DIAGNOdent® and ICDAS II achieved good reproducibility (Kw ICDAS II gravidade = 0.60 e KICDAs II atividade = 0.61; ICC DIAGNOdent® = 0.968 and showed better performance (Az ICDAS II = 0.91 e Az DIAGNOdent® = 0.95) in detection of dentine lesions (D3). The area under the ROC curve for ICDAS II was 0.67 and for DIAGNOdent® was 0,60 ) on the diagnosis of enamel lesions (D1 e D2) and for the activity criteria of ICDAS II was 0.46. The correlation with the gold standard was moderate for ICDAS II (rs = 0.515, p=0.01) and weak for DIAGNOdent® (rs = 0.355, p<0.05). The ICDAS II can be confidently used as clinical protocol for the visual examination. The DIAGNOdent® should be used as an auxiliary method for the visual examination to diagnosis of occlusal carious lesions.